The process of adjustment and coping for women in secure forensic environments - Carr, Michelle (2013)
Clinicians working with women in forensic secure environments will be acutely aware of the diverse risks, complex treatment needs and unique responsivity issues found in this multifaceted marginal group. Women make up 5% of the prison population and approx 20% of the secure forensic psychiatric population (approx 4,500 and 1,085 women respectively). What animates the studies of women is not so much numbers of offenders but the particular circumstances of the women and girls “behind” the numbers. There is a common perception that women make up such a small number of the criminal justice service (CJS) population that devising gender sensitive environments and interventions is unnecessary. However studies of patients detained in high and medium security have identified significant gender differences. Women are more likely to commit minor offenses, be diagnosed with a personality disorder, present with self injurious behavior and have suffered childhood victimization. Thus, women and girls who are caught up in the justice system enter it as a result of circumstances distinctly different from those of men.